2012
DOI: 10.1016/j.infbeh.2011.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Maternal parenting stress and mothers’ reports of their infants’ mastery motivation

Abstract: Mastery motivation is a psychological force that stimulates an individual to attempt to master a task that is challenging to him or her. This prospective longitudinal study examined the relationship between maternal stress, using the Parenting Stress Index-Short Form, and infant mastery motivation, using the Dimensions of Mastery Questionnaire, for 150 mother-infant pairs assessed at both 6- and 18-months of age. Infants of mothers with elevated stress levels at 6 months tended to show lower mastery motivation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 21 publications
0
16
0
4
Order By: Relevance
“…In addition to the relationship with mother–child affect exchanges, the fact that children's earlier mastery ratings were almost always the strongest predictor of their later mastery ratings might imply an evocative effect of children's mastery on mother–child affect exchanges. As one recent study indicated, infants' lower persistence and competence at 6 months were associated with their mothers' elevated stress one year later (Sparks, Hunter, Backman, Morgan, & Ross, ). Initial elevated stress of the mothers was also associated with infants' poorer mastery motivation one year later.…”
Section: Discussionmentioning
confidence: 98%
“…In addition to the relationship with mother–child affect exchanges, the fact that children's earlier mastery ratings were almost always the strongest predictor of their later mastery ratings might imply an evocative effect of children's mastery on mother–child affect exchanges. As one recent study indicated, infants' lower persistence and competence at 6 months were associated with their mothers' elevated stress one year later (Sparks, Hunter, Backman, Morgan, & Ross, ). Initial elevated stress of the mothers was also associated with infants' poorer mastery motivation one year later.…”
Section: Discussionmentioning
confidence: 98%
“…It is also important to consider that parent responses could be influenced by underlying factors (such as parent mental health and/or distress), factors not investigated in this study. A mother's depression is known to influence her infant's persistence with tasks, and infants of mothers with elevated stress levels tend to show lower levels of mastery motivation in toddlerhood . Additionally, parents under stress often report their children as more difficult .…”
Section: Discussionmentioning
confidence: 99%
“…A mother's depression is known to influence her infant's persistence with tasks, 28 and infants of mothers with elevated stress levels tend to show lower levels of mastery motivation in toddlerhood. 29 Additionally, parents under stress often report their children as more difficult. 27 It is likely that these environmental influences interact with each other and their relationship with children's mastery motivation is reciprocal.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, at this chronological phase of infancy, stranger anxiety typically peaks (Piaget, 1977); novel experiences for the infant at this time point may result in overt, distress, heightened vigilance, and increased demand behaviours on the primary caretaker. Reciprocally, this may manifest as maternally experienced stress (Sparks et al, 2012). Additional longitudinal research will facilitate the understanding of the directionality of this complex relationship and may offer more specifically targeted tools for child-caregiver interaction support in clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…have an impact on this dyad (Abidin, 1999). Maternal stress and maternal psychiatric well-being is associated with young children's behavioural development, such as greater infant reactivity to novelty, externalising and internalising behavioural problems, and motivation and competence in social situations (Keim et al, 2011;Mäntymaa et al, 2012;Saisto, Salmela-Aro, Nurmi, & Halmesmäki, 2008;Sparks, Hunter, Backman, Morgan, & Ross, 2012;Yaman, Mesman, van Ijzendoorn, & Bakermans-Kranenburg, 2010;Werner et al, 2012). Maternal distress may increase negative judgments about infant behaviour, and mothers reporting high parenting stress may be less responsive ('sensitive') to their infants' needs/demands (Pereira et al, 2012;Werner et al, 2012).…”
Section: Introductionmentioning
confidence: 99%